The 3(11) Battalion of the Lithuanian Police - Bubnys, Arūnas (Genocidas ir rezistencija, 2008)
The history of the 3(11) battalion can be divided into two periods: the formation and activities of the battalion in Kaunas between August 1941 and April 1942; and the battalion’s activities in Ukraine, Belarus and the time it was disbanded between May 1942 and the autumn of 1943. The battalion was formed in Kaunas at the beginning of September 1941. It guarded various military buildings, PoWs at work and the Jews ghetto in Vilijampolė. The troops of the battalion did not directly take part in the killings of the Jews. Later it was deployed in Ukraine and Belarus, where it guarded military objects and fought against Soviet partisans. The battalion was especially active in fights against the partisans and punitive operations in the district of Zhitomir and the Pripet Marches in the second half of 1942 and the beginning of 1943. During those operations the battalion might have destroyed several villages and killed scores of local residents who supported the partisans. They did not participate in the killing of Jews in Ukraine and Belarus. In the fights against the partisans and units of the Red Army the battalion suffered losses: several troops were killed, many injured and about 100 troops deserted the battalion. The battalion ceased to exist as a separate unit in the autumn of 1943. Part of the troops were included in various German units, some returned to Lithuania or deserted. A sizeable number of the troops of the 11th battalion joined the 258th Lithuanian police battalion in the spring of 1944 and served there until the autumn of 1944.
Keywords: German occupation; collaborants; Holocaust; police battalions